Self-image and your career - Ellis, Jack (Pleasantville, N.Y. : Pleasantville Media, 1988)
Encourages young people to explore their personality style, abilities, and values in order to make decision
Pt.1. A question of personality - Pt.2. The skills to do the job - Pt.3. What do you care about
Keywords: Vocational guidance